Catalysts for Syngas Production (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue on “Catalysts for Syngas Production”, included in the Catalysts open access journal, shows new research about the development of catalysts and catalytic routes for syngas production, and the optimization of the reaction conditions for the process. This issue includes ten articles about the different innovative processes for syngas production. Synthesis gas (or syngas) is a mixture of hydrogen and carbon monoxide, with different chemical composition and H2/CO molar ratios, depending on the feedstock and production technology used. Syngas may be obtained from alternative sources to oil, such as natural gas, coal, biomass, organic wastes, etc. Syngas is a very good intermediate for the production of high value compounds at the industrial scale, such as hydrogen, methanol, liquid fuels, and a wide range of chemicals. Accordingly, efforts should be made on the co-feeding of CO2 with syngas, as an alternative for reducing greenhouse gas emissions. In addition, more syngas will be required in the near future, in order to satisfy the demand for synfuels and high value chemicals.